Validation of PROMIS anxiety item bank computer adaptive test among patients with heart failure - Marblestone, Nolan; Chu, Steven; Tomei, Nicole; Lodge, Denzel; Bansal, Aarushi; Edwards, Nathaniel; Ross, Heather J.; Stehlik, Josef; Thayaparan, Desana; Fadlallah, Jad; Lee, Joshua G.; Mucsi, Istvan (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAnxiety is highly prevalent among patients with heart failure (HF), negatively affecting health related quality of life (HRQOL). The Patient-Reported Outcomes Measurement Information System (PROMIS) anxiety item bank computer adaptive testing (CAT) precisely assesses anxiety symptom severity. This study aims to assess construct validity and reliability of PROMIS-Anxiety CAT among patients hospitalized for HF.MethodsA cross-sectional convenience sample of adult patients hospitalized for HF, who completed PROMIS-A CAT, generalized anxiety disorder 7 (GAD-7), and other questionnaires electronically. Convergent validity was assessed by Spearman's rank correlation between PROMIS-A CAT, GAD-7, and other legacy measures. Known group analysis compared PROMIS-A CAT and GAD-7 scores between groups expected to have different levels of anxiety. Reliability of PROMIS-A CAT was calculated on the individual and group level from standard error of measurement, according to item response theory. Area under receiver-operating characteristics (ROC) curve and Youden's J statistic were used to identify a T-score cut-off for moderate/severe anxiety.ResultsOf 333 participants, 87 (26%) had moderate/severe anxiety based on GAD-7 score (≥ 10). Participants completed on average (median [IQR]) 4(1) vs. 7(0) items, with PROMIS-A CAT and GAD-7, respectively. PROMIS-A CAT T-scores were strongly correlated with GAD-7 scores (rho = 0.78) and moderately correlated with other legacy measures. Known-group analysis provided further support for construct validity of PROMIS-A CAT. Individual reliability for PROMIS-A CAT T-scores was >0.9 for 87% of the sample; mean reliability was 0.91. Based on ROC and Youden's J analyses, a T-score of 60 can be used to identify individuals with moderate/severe anxiety.ConclusionThese results support the validity and reliability of PROMIS-A CAT among patients hospitalized for HF.